Co-design in the Exascale Computing Project. (November 2021) - Germann, Timothy C
We provide an overview of the six co-design centers within the U.S. Department of Energy's Exascale Computing Project, each of which is described in more detail in a separate paper in this special issue. We also give a perspective on the evolution of computational co-design.